Preliminary Finite Element Analysis and Flight Simulations of a Modular Drone Built through Fused Filament Fabrication - Salvatore Brischetto (MDPI AG, 2021)
This paper discusses the architecture and preliminary design of an Unmanned Aerial Vehicle (UAV), whose actual operative scenario and required performances drive its flying configuration. The UAV is a multirotor and can be adapted to be used as a tricopter, a quadcopter, a hexacopter, and an octocopter: the number (and consequent arrangement) of the arms modify its performance. Customization is combined with the concept of additive manufacturing, as all components are designed to be produced in Fused Filament Fabrication (FFF). This approach does not limit the application scenarios of the drone; it is instead a further push in the direction of customization, as it permits continuous upgrades over time. The paper simulates four scenarios and discusses how to optimize performances such as payload, thrust-to-weight ratio, efficiency, flight time, and maximum speed through suitable configurations. Avionic components already available on the market integrate into a customizable and adaptable frame. This analysis reveals the most severe conditions for the structure, and conducts a structural validation of its performance. Validating the functional use of FFF-produced parts is challenging due to the anisotropic behavior of the parts. However, some structural elements are thin-walled and enjoy being printed with a 100% linear infill. A simplified approach to those elements has already been proposed and validated through a parallel with UniDirectional Composites, whose 2D testing procedures and methodologies have been derived and adapted. An FEA of some elements of the frame is conducted, using shell elements to discretize the geometry. A proper definition of their mechanical response is possible because the constitutive model is not isotropic a priori but reflects the behavior of the finished parts. The tensile strength variability in the material reference system is high: a component-by-component comparison proves the design to be adequate and measured to the surrounding conditions; however, it highlights the absence of a defined failure criterion.